An experimental and numerical comparative study on the uplift capacity of single granular pile anchor and rough pile in sand. Issue 4 (21st April 2022) - Joseph, Jerin; Kumar, Shailendra; Sawant, Vishwas A; Patel, Jignesh B
ABSTRACT: Granular pile anchor (GPA) is a relatively new foundation technique that is found to be effective in resisting uplift forces in expansive soils. GPA can be utilized as an economical substitute to other methods to resist the uplift loads in sandy soils. In this study, the performance of GPA and rough piles installed in the sand bed under uplift was examined using laboratory-scale model tests and numerical modelling under field-scale conditions. The laboratory-scale model tests were performed on GPA and rough pile installed in loose, medium dense, and dense sand beds by varying the embedment ratio. A numerical study was also done to check the findings from the experimental study and GPA suitability under field-scale conditions. The laboratory-scale and numerical study revealed that GPA performs better than bored pile under uplift force and can be used as an effective ground anchoring alternative.